2021
DOI: 10.1016/j.jappgeo.2021.104444
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric SAR modelling of near surface data to improve geological model in the Surat Basin, Australia

Abstract: This paper presents a study on geophysical inverse modelling for sub-surface structural properties of an unconventional hydrocarbon site that was monitored previously by Interferometric Synthetic Aperture Radar (InSAR) technology for surface deformation. A static three-dimensional geomodel along with extracted property maps replicates the depth of each underlying stratigraphic unit and structural feature with the density of each geological layer. We examine the hypothesis that integration of elastic properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The DInSAR technique enables accurate satellite monitoring under all-weather conditions and even in absence of any ground equipment [18]. There ae multiple studies [19][20][21][22][23] that used the DInSAR methodology to monitor and analyse displacements across land and structures. Moghadam et al [23], in their study performed the DInSAR stacking method at a prominent Coal Seam Gas (CSG) site, and found that the inversion of INSAR deformation maps can help in solving the uncertainties arising out of low-resolution seismic acquisitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DInSAR technique enables accurate satellite monitoring under all-weather conditions and even in absence of any ground equipment [18]. There ae multiple studies [19][20][21][22][23] that used the DInSAR methodology to monitor and analyse displacements across land and structures. Moghadam et al [23], in their study performed the DInSAR stacking method at a prominent Coal Seam Gas (CSG) site, and found that the inversion of INSAR deformation maps can help in solving the uncertainties arising out of low-resolution seismic acquisitions.…”
Section: Introductionmentioning
confidence: 99%
“…There ae multiple studies [19][20][21][22][23] that used the DInSAR methodology to monitor and analyse displacements across land and structures. Moghadam et al [23], in their study performed the DInSAR stacking method at a prominent Coal Seam Gas (CSG) site, and found that the inversion of INSAR deformation maps can help in solving the uncertainties arising out of low-resolution seismic acquisitions. Jiang et al [21], in their study compared the feasibility of using PS-InSAR, stacking and 2-pass DInSAR methodologies in identifying land subsidence at the Wuda coalfield in Northern China.…”
Section: Introductionmentioning
confidence: 99%
“…The DInSAR technique enables accurate satellite monitoring under all-weather conditions and even in absence of any ground equipment [18]. There are multiple studies [19][20][21][22][23] that used the DInSAR methodology to monitor and analyze displacements across land and structures. Moghadam et al [23], in their study performed the DInSAR stacking method at a prominent Coal Seam Gas (CSG) site, found that the inversion of INSAR deformation maps can help in solving the uncertainties arising out of low-resolution seismic acquisitions.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple studies [19][20][21][22][23] that used the DInSAR methodology to monitor and analyze displacements across land and structures. Moghadam et al [23], in their study performed the DInSAR stacking method at a prominent Coal Seam Gas (CSG) site, found that the inversion of INSAR deformation maps can help in solving the uncertainties arising out of low-resolution seismic acquisitions. Jiang et al [21], in their study, compared the feasibility of using PS-InSAR, stacking and 2-pass DInSAR methodologies in identifying land subsidence at the Wuda coalfield in Northern China.…”
Section: Introductionmentioning
confidence: 99%